COMORBIDITIES OF ISCHEMIC HEART DISEASE WITH OTHER NON-COMMUNICABLE DISEASES IN ADULT POPULATION: AGE AND RISK FACTORS ASSOCIATION - S. A. Shalnova; R. G. Oganov; A. D. Deev; A. E. Imaeva; М. М. Lukyanov; G. V. Artamonova; Т. М. Gatagonova; Yu. I. Grinshtein; D. V. Duplyakov; А. Yu. Efanov; Yu. V. Zhernakova; V. A. Ilyin; et al. (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To study the prevalence of ischemic heart disease as one of the most common cardiovascular disorders, together with arterial hypertension (AH), diabetes mellitus (DM) and liver diseases (LD) in adult (25-64 y.o.) population of selected RF regions, the variance of those with gender and age, and association of cardiovascular risk factors (FR).Material and methods. Into analysis we included the results of representative selections studies from 13 RF regions, studied according to the program of multicenter study ESSE-RF during the years 20122014; totally 21923 patients studied. Investigation included standard questioning, including anamnesis. For statistics we used applied software SAS.Results. In men the prevalence of IHD is associated with the growth of comorbidity from 0 in the age group 25-34 y. to 77% in the age 55-64 y., almost duplicating every decade. For women there is analogic tendency, less prominent. In men there are significant associations only with AH, which increases the risk of IHD 2,5 times, though in women together with AH the associations are significant for LD. Comorbidities with DM do not influence the prevalence of IHD in men and women. At the same time, any association with two diseases increases the risk of IHD >304 times. The most negative is the association of all three diseases, with which IHD is 8,7 times more prevalent, than in their absence. Using multidimensional logistic regression after correction for the age and comorbidity in the patients with IHD of both genders, there are associations revealed of high density cholesterol lipoproteids (HDL) in blood and abdominal obesity. In men there are also positive associations with smoking and negative — with increased cholesterol.Conclusion. Comorbidities of IHD with AH, DM and LD in adult population are common, are associated with the general FR, are increasing with the age. Taking modern tendencies of population ageing, it is plausible to expect an increase of the prevalence of comorbidities, that requires a necessity of the healthcare services to these changes.